New brachypterous species of Dichotomius Hope, with taxonomic notes in the subgenus Luederwaldtinia Martínez (Coleoptera: Scarabaeidae: Scarabaeinae) - Nunes, Rafael V.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2013)
An overview of the subgenus Dichotomius (Luederwaldtnia) and its species groups is presented with species groups proposed and a provisional identification key provided. Dichotomius (Luederwaldtnia) vidaurrei, a brachypterous new species from Bolivia, is described. Another brachypterous species, from Brazil, D. mysticus (Luederwaldt) is redescribed. Dichotomius paraguayanus Gandini & Aguilar is synonymized with Canthidium kelleri (Martínez, Halffter & Pereira). Some aspects of the evolution of flightlessness in Dichotomius are discussed.